Strong convergence theorem for family of minimization and monotone inclusion problems in Hadamard spaces - Izuchukwu,Chinedu (Universidad Católica del Norte, Departamento de Matemáticas, 2021)
Abstract In this paper, we introduce a modified Ishikawa-type proximal point algorithm for approximating a common solution of minimization problem, monotone inclusion problem and fixed point problem. We obtain a strong convergence of the proposed algorithm to a common solution of finite family of minimization problem, finite family of monotone inclusion problem and fixed point problem for asymptotically demicontractive mapping in Hadamard spaces. Numerical example is given to illustrate the applicability of our main result. Our results complement and extend some recent results in literature.